S14G-humanin confers cardioprotective effects against chronic adrenergic and pressure overload-induced heart failure in mice - Qi Zhao; Ming-Ming Cai; Dan Li; Bin-Yi Zhao; Shuang-Shan Zhou; Zhen-Ru Wu; Yu-Jun Shi; Li Su (Heliyon, 2023)
S14G-humanin (HNG), an analog of the mitochondria-derived peptide humanin, has demonstrated protective effects against various cardiovascular diseases. However, the specific pharmacological effects of HNG in heart failure (HF) have not been previously reported. Therefore, in this study, we aimed to investigate the potential protective effect of HNG in HF using a mouse model. HF was induced in mice through intraperitoneal injection of isoproterenol or transverse aortic constriction, followed by separate administration of HNG to assess its therapeutic impact. Our results revealed that HNG treatment significantly delayed the onset of cardiac dysfunction and structural remodeling in the HF mouse model. Furthermore, HNG administration was associated with reduced infiltration of inflammatory cells, improved myocardial fibrosis, and attenuation of cardiomyocyte apoptosis in the treated cardiac tissues. Additionally, we identified the involvement of the transforming growth factor-beta signaling pathway in the beneficial effects of HNG in isoproterenol-induced HF mice. Collectively, these findings underscore the therapeutic potential of HNG in preventing the progression of HF, as demonstrated in two distinct HF mouse models.